PENETAPAN KADAR FENOLIK DAN FLAVONOID SERTA AKTIVITAS INHIBISI ENZIM TIROSINASE FREEZE DRY JUS BUAH JAMBLANG (Syzygium cumini (L.) Skeels) - Nani Suryani; Dimas Danang Indriatmoko; Alfi Mahmudah; Dodik Efendi (Fakultas Farmasi Universitas Setia Budi, 2022)
The skin is the largest organ that protects the body from various traumas such as thermal, chemical, and ultraviolet radiation. Melanin biosynthesis is the conversion of L-Tyrosine (4-hydroxyphenylalanine) to L-DOPA (L-3,4-dihydroxyphenylalanine) with the help of the tyrosinase enzyme. Phenolics and flavonoids significantly affect the inhibition of tyrosinase activity. Phenolics and flavonoids are thought to be contained in the fruit of Syzygium cumini. This study aimed to determine the levels of phenolics and flavonoids and to determine the tyrosinase enzyme inhibitory activity of freeze-dried S. cumini fruit juice. The method used to determine the levels of phenolics and flavonoids using UV-Vis spectrophotometry and tyrosinase inhibition test using in vitro ELISA (Enzyme Linked Immunosorbent assay). S. cumini contains total phenolic is 0.13155 mg GAE/g and total flavonoid is 37,333 mgQE/g. Freeze dry fruit juice of S. cumini has potential as a tyrosinase enzyme inhibitor at 31.25 ppm (14.846%), 62.5 ppm (16.246%), 125 ppm (19.238%), 250 ppm (22.059%), 500 ppm (25.665). %), 1000 ppm (32.283%) and 2000 ppm (44.188%).